Mapping humidity plume over local climate zones in a high-altitude tropical climate city, Brazil - Masiero, Erico; Souza, Léa Cristina Lucas de (Ambiente Construído, 2018)
<span style="font-family: ’Times New Roman’,serif; font-size: 12pt; mso-bidi-font-size: 10.0pt; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;" lang="EN-US">The aim of this research is to detect the cooling effects of water body evaporation in different Local Climate Zones (LCZs) in a tropical area. We attempted to register the humidity action over the urban environment caused by the evaporation of an urban lake according to the typical regional winds. The method was developed on the basis of three steps: the physical characterization of the LCZ conditions, the definition of data collection procedures with the mesoclimate analysis; and the interpretation of data by mapping the local measured variables. The study also included a microclimate data collection campaign aimed to evaluate more specifically the typical behaviourof the air temperature and absolute humidity in areas near the water body and in environments of the urban centreof São Jose do Rio Preto in Brazil. The air temperature range in areas near the water surface presented values lower than the denser areas, reaching differences close to 4 °C, and as the environment becomes drier and impermeable, the air temperature tended to be higher. This fact highlights the need to being outlined urban occupation strategies for improving the thermal quality of the built environment, mainly in cities located in regions with a predominantly high altitude tropical climate.